The Clinical Translation Gap in Child Health Exercise Research: A Call for Disruptive Innovation. Issue 1 (11th August 2014) - Ashish, Naveen; Bamman, Marcas M.; Cerny, Frank J.; Cooper, Dan M.; D'Hemecourt, Pierre; Eisenmann, Joey C.; Ericson, Dawn; Fahey, John; Falk, Bareket; Gabriel, Davera; Kahn, Michael G.; Kemper, Han C.G.; et al.
Abstract In children, levels of play, physical activity, and fitness are key indicators of health and disease and closely tied to optimal growth and development. Cardiopulmonary exercise testing (CPET) provides clinicians with biomarkers of disease and effectiveness of therapy, and researchers with novel insights into fundamental biological mechanisms reflecting an integrated physiological response that is hidden when the child is at rest. Yet the growth of clinical trials utilizing CPET in pediatrics remains stunted despite the current emphasis on preventative medicine and the growing recognition that therapies used in children should be clinically tested in children. There exists a translational gap between basic discovery and clinical application in this essential component of child health. To address this gap, the NIH provided funding through the Clinical and Translational Science Award (CTSA) program to convene a panel of experts. This report summarizes our major findings and outlines next steps necessary to enhance child health exercise medicine translational research. We present specific plans to bolster data interoperability, improve child health CPET reference values, stimulate formal training in exercise medicine for child health care professionals, and outline innovative approaches through which exercise medicine can become more accessible and advance therapeutics across the broad spectrum of child health.